The Influence of Oxytocin Massage with Uterus Involution Mother’s Post Partum Primigravida in Panembahan Senopati Bantul’s Public Hospital,Yogyakarta - Fauziah H. Wada; Mara Imbang Satriawan Hasiolan (Jurnal Kesehatan, 2020)
Efforts to prevent postpartum hemorrhage can be done by administering oxytocin in the third stage. Another way to stimulate the release of oxytocin is the oxytocin massage is a method to stimulate oxytocin, so it expected to increase breastfeeding and spending accelerates uterine involution. The aims of study to determine the effect of oxytocin massage on uterine involution postpartum mother primigravida. Design of this research is a Quasi Experimental posttest only design with control group. Technique to taking the sample using purposive sampling with 30 respondents were divided into 2 groups. intervention group (p = 0.000), whereas the control group was not significant (p = 0.865). There are significant differences in the first 24 hours until day 4 and day 4 until day 7 uterine involution in the intervention group and the control group (p = 0.000). The conclusion of this research is a significant difference between the administrations of oxytocin massage on uterine involution postpartum primigravida mothers in Panembahan Senopati hospitals in Bantul, Yogyakarta.